Relationships Between Certain Diagnostic Indices of Salt Affected Soils of Indo-Gangetic Alluvial Region - Singhla, S K; Bhargava, G P; Gupta, I C (Annals of Arid Zone, 2016)
In the salt affected soils of the Indo-Gangetic alluvial region, the electrical conductivity of 1 to 2 soil water suspension (BC2) is seen to be highly correlated with electrical conductivity of the saturation extract (BCe), total cation concentration (TCC) and soluble sodium concentration (SSC), with and without saturation percentage (SP). both in chloride soils as well as in carbonate soils. The ratio of ECe/BC2 decreases with the increase in SP. Based upon simple and multiple regression of tho relationships, prediction equations have been worked out.